ROCKET INSTRUMENTATION FOR THE STUDY OF A POLAR CAP ABSORPTION EVENT: PCA-69. - Baker,Kay D.; Burt,David A.; Howlett,L. Carl; Allred,Glenn D. (1970)
An ionospheric measurements program (PCA-69), utilizing 41 scientifically instrumented, sequentially launched rockets, was conducted from the Churchill Research Range, Manitoba, Canada. The purpose of the program was to obtain measurements of ionospheric parameters and ionizing input fluxes during a polar cap absorption event. The event investigated occurred on 2, 3, and 4 November 1969, and produced initial levels of absorption ranging to >15 db with subsequent lower levels during its decay. A large portion of the instrumentation of 15 of the 41 rockets was provided by Upper Air Research Laboratory, University of Utah under Contract F19628-67-C-0275. This report describes that instrumentation, provides instrument specifications, and gives a general overview of the entire program and its history. (Author)